Bisphenol A increases TLR4-mediated inflammatory response by up-regulation of autophagy-related protein in lung of adolescent mice. (April 2021) - Wang, Simeng; Yang, Yilong; Luo, Dan; Zhai, Lingling; Bai, Yinglong; Wei, Wei; Sun, Qi; Jia, Lihong
Abstract: In previous studies we found that bisphenol A (BPA) aggravated OVA-induced lung inflammation. The aim of this research was to determine whether BPA exposure alone also induced inflammatory response in the lungs, which mechanism was associated with TLR4/NF-κB signaling pathway and the activation of mTOR-mediated autophagy. Female C57BL/6 mice aged 4 weeks were randomly divided into three groups (10/group): control group, 0.1 and 0.2 μg mL −1 BPA groups. BPA induced the pathological changes in the lung and increased the levels of cytokines and inflammatory cells, as well as affected autophagy related proteins expression. In addition, the RAW264.7 cell culture experiment was conducted in order to confirm the role of autophagy. We found that BPA can enhance autophagy flux by enhancing autophagosome formation. It was further confirmed the details of the mechanism of action with chloroquine (CQ, a compound that inhibits the fusion of autophagosomes and lysosomes) intervention. The inhibition of autophagy led to down-regulation of expression levels associated with inflammation. This research results indicated that BPA induced inflammatory response in vitro and in vivo, and its mechanism may be related to TLR4/NF-κB signaling pathway and the activation of mTOR-mediated autophagy. After autophagy was suppressed, the inflammatory response also weakened. Our findings provide a new perspective into the mechanisms underlying inflammatory responses induced by the environmental exposure. These findings indicate that therapeutic strategies targeting autophagy may provide a new method for the treatment of inflammatory diseases. Graphical abstract: Image 1 Highlights: BPA induces inflammatory response in developmental female mice and RAW264.7 cells. Inflammation is related to TLR4/NF-κB and mTOR-mediated signaling pathway. After CQ inhibits autophagy, the inflammatory response is weakened. The activation of autophagy and TLR4/NF-κB signaling pathway induces inflammation.